SHEAR MECHANISM AND SHEAR STRENGTH PREDICTION OF REINFORCED CONCRETE T-BEAMS (Jurnal Teknologi (Sciences & Engineering), 2016)
Shear failure in reinforced concrete beams are sudden failures and should be avoided at all times. However, the shear behaviour of a reinforced concrete beam is a complex mechanism and requires in-depth study. To understand the shear mechanism, two (2) simply supported reinforced concrete T-beams, BEAM1 and BEAM2 were tested until failure subjected to a 4-point bending test. Both beams were designed to the recommendations and specifications of two (2) established design codes by ACI318-08 and Eurocode2 (EC2). The study comprises of two reinforced concrete T-beams having similar variables and parameters with longitudinal reinforcement of Ï = 2.15% and shear span-to-effective depth ratio (av/d) of 3.5. Shear reinforcement or stirrups has been added to the specimen and its spacing of stirrups has been provided with the provisions of the codes. The findings from the study indicate that ACI318-08 and EC2 design codes shows significant differences in determining its shear strength capacity Vn and concrete shear resistance Vcof the T-beams. However, both results were less conservative in its prediction when compared to the experimental results.Â